The Effect of Information Releases on the Pricing and Timing of Equity Issues - Korajczyk, Robert A.; Lucas, Deborah J.; McDonald, Robert L. (Review of Financial Studies, 1991)
With time-varying adverse selection in the market for new equity issues, firms will prefer to issue equity when the market is most informed about the quality of the firm. This implies that equity issues tend to follow credible information releases. In addition, if the asymmetry in information increases over time between information releases, the price drop at the announcement of an equity issue should increase in the time since the last information release. Using earnings releases as a proxy for informative events, we find evidence supporting these propositions.